Broadening the Offering Choice of Corporate Bonds in Emerging Markets : Cost-Effective Access to Debt Capital - Endo, Tadashi (World Bank, Washington, DC, 2012)
The development of corporate bond markets has been constrained in many emerging economies, partly because the regulatory model is implicitly designed for stand-alone public offerings. Corporate bonds are intrinsically more suitable for non-retail investors than for retail investors. Nonetheless, the prevailing regulatory model puts an excessive emphasis on disclosure and investor protection as well as government oversight, regardless of targeted investors. Such a non-differentiating regulatory approach disconnects issuers from investors by considerably raising opportunity costs to issuers. Broadening the choice of offering methods would lower corporate bond issuance costs, thereby allowing more issuers to finance their investments with bond issues. Additional forms of offerings are traditional private placements, institutional offerings, and shelf registration facilitated by integrated disclosure.